Advancements in Early Alzheimer’s Treatment: Narrative Review about Lecanemab (Leqembi ®) - Adrianna Muciek; Martyna Mocarska; Anna Orłowska; Katarzyna Strakowska; Laura Opalska; Anna Maryńczak; Jan Mencel; Nicole Nitschke (Quality in Sport)
Alzheimer's disease represents one of the most significant challenges in the field of neurology, affecting millions of individuals worldwide. In pursuing efficacious treatments, lecanemab has emerged as a promising therapeutic option. This pioneering monoclonal antibody targets and reduces amyloid-beta plaques in the brain, a defining feature of Alzheimer's disease. By addressing one of the fundamental causes of the disease, lecanemab represents a novel approach to slowing its progression.